Usability testing of e-learning system: a case study on college e-learning system (CeL) system in Tunku Abdul Rahman University College, Johor Branch Campus / Noriza Satam - Satam, Noriza (2016)
Tunku Abdul Rahman University College (TARUC) is a private higher education institution that provide education at tertiary level in various field such as accounting, business, food science, computer science, built environment, mass communication, and hospitality management. Like any other higher education institutions, TARUC have an e-learning system namely College E-Learning System (CeL) that is designed to enable teaching and learning through the use of internet technologies. The existence of a good e-learning system will give significant strategic advantages to an educational institution. The interface of e-learning system should be easy to use where student will be able to retrieve the content and not only focus on the interaction with the system. Therefore, usability plays an important role in the success of every e-learning system. However, based on preliminary study conducted with some students, they found out that it is difficult for them to acquire relevant information to their studies. Furthermore, usability testing has not been conducted since the introduction of new CeL in September 2013. Therefore, this project aims to identify the usability problems of CeL and provide recommendations to improve the usability of CeL. This project specifically focuses on TARUC Johor Branch Campus. Usability testing was conducted on five (5) participants where they had been interviewed and performed series of tasks to identify the usability problem of CeL. The results show that interface design of CeL is dull and unattractive. Certain materials is not accessible and important information not been included in the e learning system. The outcome of this project would assist the Communication and Information Technology Centre (CITC) to identify usability problems that exist and provide a rcommendation for them to improve the CeL. For future project, the usability testing could be extended to other branch campuses as well. Through conducting the usability testing in all TARUC campuses, comparative studies could be made possible. The studies could involve students from different faculties or focus on CeL usage among lecturers to see the usability of CeL from different perspectives.